Syed Qasim Ahmad Andrabi: A True Islamic Missionary - Ali*, Damsaz (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Syed Qasim devoted his whole life for the betterment of the people. Message of Tuwhid was disseminated by him among the common masses. Some novel methods were adopted to boost the economic setup of people. Various Maktabas, Madrasas and Mosques were constructed in the area. Large numbers of people approached him and simultaneously were influenced by his teachings. People used to come to Syed from far and wide areas of the valley and accordingly a true sincere Islamic brotherhood flourished. This Islamic brotherhood continued from generation to generation and people at present and even in future will remember the contribution of Syed. Some of his descendants left the valley and settled down at various parts.